Inhibitory Activity of Essential Oils of Mentha spicata and Eucalyptus globulus on Biofilms of Streptococcus mutans in an In Vitro Model - Guillermo Ernesto Landeo-Villanueva; María Elena Salazar-Salvatierra; Julio Reynaldo Ruiz-Quiroz; Noemi Zuta-Arriola; Benjamín Jarama-Soto; Oscar Herrera-Calderon; Josefa Bertha Pari-Olarte; Eddie Loyola-Gonzales (MDPI AG, 2023)
The aim of this study was to evaluate the inhibitory activity of the commercially available essential oils of Mentha spicata (spearmint) and Eucalyptus globulus (eucalyptus) on Streptococcus mutans ATCC 25175 biofilms in vitro, emulating dental plaque conditions. The composition of the essential oils (EOs) was determined using gas chromatography coupled with mass spectrometry (GC-MS), with the main metabolites being Carvone (57.93%) and Limonene (12.91%) for Mentha spicata and 1,8-Cineole (Eucalyptol) (65.83%) for Eucalyptus globulus. The inhibitory activity was evaluated using the methods of agar-well diffusion and colorimetric microdilution. The inhibition halos were 18.3 ± 0.47 mm and 27.0 ± 0.82 mm, and the MICs were 1.8484 mg/mL and 1.9168 mg/mL for the EOs of Mentha spicata and Eucalyptus globulus, respectively. The activity against the biofilms was evaluated on a substrate of bovine enamel pieces using a basal mucin medium (BMM) in anaerobic conditions with daily sucrose exposition cycles in order to emulate oral cavity conditions. The EOs were applied in a concentration of 0.5% in a sterile saline vehicle with 1% polysorbate 20. After 72 h of cultivation, a significant reduction was observed (p < 0.001%) on the biofilm biomass, which was evaluated by its turbidity in suspension and using a count of the recoverable organisms with regards to the control. The effects of the Eos were not significantly distinct from each other. The EOs showed antimicrobial activity against both the Streptococcus mutans planktonic and biofilm cultures. Thus, EOs may have great potential for the development of pharmaceutical and sanitary products for oral health.